2020
DOI: 10.1186/s12876-020-01575-7
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of early intervention on the bowel damage and intestinal surgery of Crohn’s disease, based on the Lémann index

Abstract: Background Clinicians aim to prevent progression of Crohn’s disease (CD); however, many patients require surgical resection because of cumulative bowel damage. The aim of this study was to evaluate the impact of early intervention on bowel damage in patients with CD using the Lémann Index and to identify bowel resection predictors. Methods We analyzed consecutive patients with CD retrospectively. The Lémann Index was determined at the point of inc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Observational studies have demonstrated that LI progressively increases since diagnosis [ 14 ], with median scores of 2.3 (IQR, 1.2–3.9) at first evaluation, 3.5 (IQR, 1.2–8.6) at 2 to 5 years after diagnosis, and 8.3 (IQR, 1.2–12.1) at 5 to 10 years after diagnosis [ 16 ]. It has also been shown as a prognostic marker, as higher scores at diagnosis predict the need of surgery during the first year [ 21 ], so it has been suggested that these cases should be proactively treated and monitored carefully to prevent progressive bowel damage [ 16 , 17 , 22 ]. Similar observations have been done even in patients considered as early CD (< 24 months disease duration with no previous medical therapy or surgery), in whom any relative increase on LI was associated with a worse prognosis [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Observational studies have demonstrated that LI progressively increases since diagnosis [ 14 ], with median scores of 2.3 (IQR, 1.2–3.9) at first evaluation, 3.5 (IQR, 1.2–8.6) at 2 to 5 years after diagnosis, and 8.3 (IQR, 1.2–12.1) at 5 to 10 years after diagnosis [ 16 ]. It has also been shown as a prognostic marker, as higher scores at diagnosis predict the need of surgery during the first year [ 21 ], so it has been suggested that these cases should be proactively treated and monitored carefully to prevent progressive bowel damage [ 16 , 17 , 22 ]. Similar observations have been done even in patients considered as early CD (< 24 months disease duration with no previous medical therapy or surgery), in whom any relative increase on LI was associated with a worse prognosis [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Throughout the years, several authors have evaluated the impact of targeting early CD on disease outcomes ( Table 1 ). Most of the available evidence comes from the use of anti-TNF drugs, either alone (22 12 21 , 23 25 , 29 , 31 , 32 , 34 , 35 , 36 , 37 , 38 , 41 out of 29 studies) or in combination with immunosuppressants (7 7 , 17 , 30 , 34 , 38 , 39 , 40 ); the single use of immunosuppressants was evaluated in five studies, 17 , 21 , 28 , 33 , 38 while vedolizumab was studied once. 22 Although ‘early disease’ definition and the outcomes sought varied widely, data from observational studies and from post-hoc analysis of RCTs have shown that patients who received therapy in the early stage of disease have better outcomes than those who received treatment later.…”
Section: Early Intervention and Impact On Prognosismentioning
confidence: 99%
“… 14 , 21 , 41 Besides that, some authors have stated that intervention within 18 months after CD diagnosis may prevent and even reverse bowel damage. 40 On the other hand, the impact of early treatment on patients’ quality of life, work productivity, and disability remains largely unexplored.…”
Section: Early Intervention and Impact On Prognosismentioning
confidence: 99%
“…The literature is controversial regarding the optimal timing of surgery. Even the period that is taken into account to define a surgical intervention as early is inconstant, varying from 6 to 18 months after CD diagnosis (18,19). Earlier surgical approaches would be related to the performance of technically easier procedures, smaller resections and consequently lower postoperative complications.…”
Section: Timing Of Surgerymentioning
confidence: 99%